Prescribing Pattern of Drugs in Geriatrics Patients Using Beers Criteria - Rijal, Saibijaya; Adhikari, Kajiram; Sigdel, Deepak; Mallik, Shyam Kumar (Journal of Nepal Health Research Council, 2019)
Background: Geriatric people particularly those with multiple co-morbid condition may result in polypharmacy which can be associated with use of potentially inappropriate medication. This study aims to understand about prescription pattern and to find out inappropriate medication used in geriatric patients using Beer’s criteria 2012. Methods: A cross sectional study was conducted from May 2018 to Aug 2018 in Koshi Zonal Hospital in Biratnagar. Data of all elderly patients greater above or equal to 60 years those were admitted to General Medical Ward during this period was analyzed. Results: Eighty-six percent of the prescriptions were appropriate and 14% were inappropriate. Seventy-seven percent of drugs belong to Group I of Beer’s criteria (Potentially inappropriate medication use in older adults), 23% of drugs belong to Group III (Potentially inappropriate medication to be used with caution in older adults) and no drugs fall under Group II (Potentially inappropriate medication use in older adults due to Drug-Disease or Drug-Syndrome interactions that may exacerbate the disease or syndrome) of Beer’s criteria. Conclusions: Potentially inappropriate medication was found out to be 14%. The use of inappropriate medications can be avoided using Beer’s criteria 2012 which is important clinical tool that can be used by physicians, pharmacist and other health care professionals. Keywords: Beer’s criteria; geriatric; potentially inappropriate medication; prescribing pattern.